Using Canva to improve drawing for elementary school - Maharromiyati; Sani Suhardiman; Ertyn Tyas Prabandari; Laily Rahmah; Asriyah (Universitas Negeri Semarang, 2024)
This study aims to evaluate the effectiveness of using Canva as a digital drawing tool in improving drawing skills and engagement of elementary school students. Through quantitative design and descriptive analysis of data collected from 48 teachers in various public elementary schools in Central Java, the study found that the use of Canva had a significant positive impact on students' understanding of design concepts, creativity, and engagement. A total of 45.8% of respondents strongly agreed and 50% agreed that Canva helps students understand basic design concepts better. In addition, 56.3% of respondents agreed and 37.5% strongly agreed that students' creativity improved after using Canva, indicating that the platform provides ample space for students to experiment with different drawing techniques. In terms of engagement, 47.9% of respondents strongly agreed and 39.6% agreed that using Canva increased student engagement in art projects compared to traditional methods. In addition, 60.4% of respondents agreed and 35.4% strongly agreed that Canva allows for more effective collaboration between students on drawing projects. However, while the benefits are significant, most respondents feel that additional training is needed to optimize the use of Canva in art teaching. These findings show that integrating Canva into the drawing curriculum not only improves students' artistic skills, but also prepares them for success in the digital world of the future.